Creating opportunities for untethered learning. Issue 4 (8th August 2018) - Schuck, Sandy; Maher, Damian
ABSTRACT: This article discusses the use of mobile devices by teachers in two Australian schools. It builds on a theoretical framework which considers the location of mobile learning with respect to time and space. The research used a qualitative methodology in which observations, interviews and document analysis were conducted. The study found that the physical and virtual spaces that were used were different from those used in other lessons. Mobile learning facilitated autonomous learning by students, collaboration with their peers and engagement in topics of interest to them. The study found that students and teachers adopted new roles when using the devices, and were untethered from their conventional learning spaces of the classroom. Learning changed in nature and was aligned with contemporary practices in education.